Graded Sensitivity to Vowel Mispronunciations in Newly Learned Words. - Massar, Molly; Conwell, Erin (Language & Speech, 2026)
Studies of word recognition have demonstrated that listeners show graded sensitivity to mispronunciations of consonants in words, as well as better mispronunciation detection for more familiar words. However, little research has considered whether this graded sensitivity to mispronunciation can also be found for vowels and how that might interact with word familiarity. In this study, 73 English-speaking adults learned novel consonant-vowel-consonant (CVC) labels for novel objects, with varying amounts of exposure to those labels during learning. Participants were then tested on their learning of these word-referent pairs, as well as on their responses when these newly learned words were mispronounced with a vowel that either had the same backness (±) as the original vowel (small mispronunciation) or the opposite backness as the original vowel (large mispronunciation). Participants reliably matched learned words to referents when the words were correctly pronounced but sometimes selected a distractor referent when the words were mispronounced, suggesting interpretation as a new word. Larger mispronunciations, particularly of more familiar words, increased the likelihood of distractor selection. These findings add to the growing body of evidence that perception of mispronounced words is affected by both lexical familiarity and degree of mispronunciation.